Etnobotany of Plants With Useful Medicine in Gumanano Village, Sub-District Mawasangka District Central Button - Yanti Yanti; Maretik Maretik (Jurnal Biologi Tropis, 2022)
Gumanano Village, Mawasangka District is an area that has biodiversity, one of which is medicinal plants. Communities in Gumanano Village have used medicinal plants to prevent and treat various types of diseases that have been passed down from generation to generation. aims to inventory the types of medicinal plants used by the people in Gumanano Village, to know the plant organs used, the method of processing and utilization (ethno-medical). This type of research is classified as qualitative descriptive research, namely research that describes the research data qualitatively. The method used in this research is interview and exploration methods, namely field investigations to collect comprehensive data/information about the types of medicinal plants, plant organs used, how to process and use medicinal plants in Gumanano Village, Mawasangka District. The results showed 37 types of medicinal plant species consisting of 22 families. Parts of plants used as medicine in Gumanano Village are leaves, fruit, tubers, roots, stems, bark, rhizomes, tuber skin and seeds. Methods of processing plants as medicine are boiled, grated, grown, kneaded, scraped, drunk, squeezed, chewed, mashed, and cooked. The benefits of medicinal plants are used for various diseases such as fever, external injuries, red eyes, high blood pressure, measles, constipation, vomiting blood, coughs, diabetes, sarmpa and antidote, kidney stones, gout, canker sores and toothache, headache , tinea versicolor, fever, dysentery, heart disease, intestinal worms, ulcers, vomiting blood, eye medicine, cough, stomach pain, lowering high blood pressure, vaginal discharge, broken bones, kidney stones, postpartum, ulcers, and jaundice.